Intensifying university industry collaboration through technology sharing within the Malaysian perspective - Ragupathy, Darshana Kumari (2020)
Innovation is the cornerstone of success for economic advancement primarily in emerging countries. Malaysia resorts to both universities and industries to collaborate in a more engaging, coherent and concentrated mode to accelerate innovation growth. Despite the myriad of collaborations, the return of investments has been marginal. This illustrates a mismatch between the demands of both the university and industry. On that grounds, it is important to address this research gap, for it will provide insights to improve universities’ and industries’ understanding in intensifying University Industry Collaborations to spur innovation. The significant contribution of this study is the emerged framework that establishes vital insights on the need to understand the economic landscape and placing technology sharing as a multiplying factor for th e intensification of UIC. The purpose of this study is to identify variables which foster University Industry Collaborations. This study further measures the outcome from Technology Sharing efforts on knowledge, performance, and competitiveness improvements in a University Industry Collaboration. Substantially this study develops and evaluates the framework on intensifying the University Industry Collaboration landscape. The conceptual theoretical framework was tested using empirical data gathered from 80 Small and Medium manufacturing companies, 20 Public Universities, and 41 Anchor manufacturing companies, through survey questionnaires. The fostering and multiplying factors were analysed using frequency analysis to reorient and capsulate variables associated to research objectives, and weightages to illustrate the intensity of the respondent companies’ contribution to the economic value chain. Further inferential statistics were applied to determine statistical evidence on the outcomes of technology sharing on knowledge, performance and competitiveness improvement. Mathematical modelling was also used to scientifically represent and evaluate the framework. The results revealed that appropriate research infrastructure, incentives to collaborate, and the need to understand the economic landscape were fundamental variables to industries meanwhile, universities pointed out the importance of human capital to do research and industry willingness as the primary factors in fostering collaboration. The results further revealed that Technology Sharing improved knowledge and performance for Anchor companies meanwhile, competitiveness also improved for Small and Medium manufacturing companies. Importantly, through the mathematical model, results revealed Technology Sharing as an important multiplying factor that intensifies University Industry Collaboration. It is paramount for University Industry Collaborations to be demanddriven and augmented with an understanding of significant fostering factors. With the purpose of intensifying University Industry Collaborations, Technology Sharing acts as an epilogue. The multiplying factor magnifies the collaboration to create a robust outcome. Technology Sharing proofs to drive private investments and allow knowledge, performance, and competitiveness improvement of industries in view of continuous innovation development within the economic landscape.